Evaluation of the PFA-100® System in the Diagnosis and Therapeutic Monitoring of Patients with von Willebrand Disease - Cattaneo, Marco; Federici, Augusto B.; Lecchi, Anna; Agati, Barbara; Lombardi, Rossana; Stabile, Federica; Bucciarelli, Paolo (Thrombosis and Haemostasis, 1999)
We have evaluated platelet function at high shear with the PFA-100® system in different subtypes of von Willebrand disease (vWD), before and after the intravenous infusions of desmopressin or a factor-VIII/von Willebrand factor (vWF) concentrate. Closure times with the PFA-100® system were determined for both the collagen/ADP and the collagen/epinephrine cartridges in 52 patients with vWD (9 type 1 “platelet normal”, 5 type 1 “platelet-discordant”, 8 type 1 “platelet-low”, 6 type 2A, 9 type 2B, 6 type 2M Vicenza, 6 type 3 and 3 acquired vWD) and 40 controls. Measurements were repeated 1 and 4 h after the i.v. infusion of desmopressin (0.3 μg/Kg) in 26 patients with types 1, type 2M Vicenza or type 2A vWD, or of a factorVIII/vWF concentrate (Alphanate HT, 60 U/Kg) in 4 patients with type 3 vWD. At all time points, vWF plasma levels and the bleeding time (Symplate II) were also determined. Baseline closure times were longer in vWD patients than in controls with both the collagen/ADP and the collagen/ epinephrine cartridges. The sensitivity of the PFA-100® system (88% and 87% with the two cartridges) was higher than that of the bleeding time (65%). Treatment with desmopressin normalized the closure times in patients with type 1 “platelet-normal” or type 2M Vicenza vWD, had no significant effects in patients with type 1 “platelet-low”, type 1 “platelet-discordant” or type 2A vWD. Infusion of a factorVIII/vWF concentrate in patients with type 3 vWD slightly shortened their prolonged closure times. In general, changes in PFA-100® were paralleled by shortenings of the bleeding times and increases in plasma vWF levels. The PFA-100® test reflects vWF-dependent platelet function under high shear stress and could be useful in the diagnosis and therapeutic monitoring of patients with vWD.